Sustainability, Evaluation, and Credentials - Andy Rowe; Juha I. Uitto (The Evaluation Center at Western Michigan University, 2023)
While there is clear demand for sustainability-ready evaluation in which environmental impacts are integrated, a major gap exists between this desire and reality. Stock takings show that environmental sustainability is rarely addressed by evaluations. For this to happen, a significant adaptation in how evaluation is organized and conducted is needed, and evaluators, commissioners and evaluation users must take an interest in sustainability. Competencies of individual evaluators and firms must be enhanced, but this is not sufficient. Sustainability-ready evaluation requires interdisciplinary competencies and collaboration.